INVESTIGATING THE USE OF PROJECT-BASED LEARNING AND STUDENTS' SATISFACTION IN THE TEACHING OF DESCRIPTIVE TEXTS: A CASE STUDY AT MTS AL-IHSAN KRIAN - Arbi, Anggun Purnomo (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Researchers widely agree that project-based learning, an effective and strongly advised instructional strategy, can foster intense engagement and enhance students' learning experiences. In order to teach descriptive text at MTS Al-Ihsan Krian during the academic year 2021-2022, this study investigated the implementation of project-based learning (PjBL) and how students responded to its use. Students from MTS Al-Ihsan Krian's 7th grade were the study's subjects. The research employed a descriptive-qualitative approach to collect data from observational findings and responses from students collected via a questionnaire. The main source of data for this study was the teaching and learning process. The primary instrument was the researcher, who was assisted by secondary instruments like questionnaires and field notes from observations. PjBL's implementation has been found to have been successful based on observations, and the findings have shown both advantages and disadvantages. According to the survey results, students at MTS Al-Ihsan Krian responded favourably to the implementation of project-based learning, highlighting the positive impact it has on learning descriptive text. On the basis of the research findings, it is recommended that educators at MTS Al-Ihsan Krian keep encouraging and incorporate project-based learning into their descriptive text teaching methodologies. This strategy has demonstrated its potential for increasing student engagement, fostering collaborative skills, and cultivating a deeper comprehension and application of knowledge